Different healthy habits between northern and southern Spanish school children - Arriscado, Daniel; Knox, Emily; Zabala, Mikel; Zurita-Ortega, Felix; Dalmau, Jose Maria; Muros Molina, Jose Joaquin (Springer Verlag, 2017)
Aim: Healthy habits are influenced by several factors such as, geographical location. The aims of this study were to describe and compare healthy habits within two populations of sixth-grade primary school children (aged 11-12 years) from Northern and Southern Spain. Subject and Methods: A cross-sectional study using two representative samples of school children was conducted. Participants came from Logroño (n=329), in the North and Granada (n=284), in the South of Spain. Socio-demographic and anthropometric variables, adherence to the Mediterranean diet, aerobic fitness, and healthy lifestyles were recorded. Results: Boys reported higher level of physical activity and aerobic fitness than girls (p=0.000). Southern school children reported significantly higher adherence to the Mediterranean diet (♀: p=0.041; ♂: p=0.008), and lower aerobic fitness (♀: p=0.000; ♂: p=0.042) and hours of nightly sleep (♀: p=0.008, ♂: p=0.007) than Northern school children. Southern boys also reported lower levels of physical activity (p=0.013). There were slight or moderate correlations among all habits measured (physical activity, diet, screen and sleep time). Additionally, physical activity level was inversely related to body mass index in Northern boys (p=0.020) and Southern girls (p=0.024). Conclusions: Results showed differences in physical activity, eating and sleep habits, and aerobic fitness, according to geographical location. The relationships found among lifestyle habits indicate the need of health promotion interventions nationally and considering the differences discussed here.